Mast Cells in Allergic Asthma and Beyond - Sebastian Reuter; Michael Stassen; Christian Taube (2010)
Mast cells have been regarded for a long time as effector cells in IgE mediated type I reactions and in host defence against parasites.However, they are resident in all environmental exposed tissues and express a wide variety of receptors, suggesting that these cells can also function as sentinels in innate immune responses.Indeed, studies have demonstrated an important role of mast cells during the induction of life-saving antibacterial responses.Furthermore, recent findings have shown that mast cells promote and modulate the development of adaptive immune responses, making them an important hinge of innate and acquired immunity.In addition, mast cells and several mast cell-produced mediators have been shown to be important during the development of allergic airway diseases.In the present review, we will summarize findings on the role of mast cells during the development of adaptive immune responses and highlight their function, especially during the development of allergic asthma.